ANALISIS KUALITAS AIR MINUM DARI DEPOT AIR MINUM AIR MINUM ISI ULANG (DAMIU) DI LINGKUNGAN INSTITUT KESEHATAN DELI HUSADA DELITUA TAHUN 2018 - Viktor Edyward Marbun (Jurnal Penelitian Kesmasy, 2021)
Study of drinking water from a refill drinking water depot at the Deli Husada Delitua Health Institute has been conducted. The quality of drinking water is analyzed based on the aspect of temperature, pH, E.coli and Bacteri Coliform to see the feasibility of refill drinking water with PERMEKES No. 492 in 2010 About drinking water requirements. Sampling is done at 3 points of drinking water source once. Based on result of temperature testing that to three points of Drinking Water Depot being sampled meet the quality standard according to the prevailing regulations that is 25OC ± 3OC, requirement of drinking water based on pH of three points in sample also meet the applicable quality standard that is 6.5-8.5. based on Biological parameters of e.coli content there is one point that does not meet drinking condition, there is e.coli of <1 with required standard of 0 / 100mL. Judging from the content of coliform bacteri there are two sample points that do not meet the requirements, contained <1 / 100ml - 1.2 / 100ml bacteri coliform with required quality standard of 0 / 100ml. The results showed that only one semester of water depot fulfilled the water criteria from 3 points of refill drinking water depot (DAMIU) in the Deli Husada Delitua Health Institute in accordance with Permenkes. 492 Year 2010 about criteria of drinking water in terms of temperature, pH, content E.coli and Total Bacteri Coliform, Therefore, it is necessary to improve the quality of drinking water sources.